Gestão integrada do turismo no espaço rural - Mendonça, Maria Cristina Angélico de (Universidade Federal de São Carlos, 2006)
The general objective of this work is suggest an analytical model of managing tourist clusters potencial that support the people involved with the activity to reach decisions that help with aspects connected to integrated managing, to development and to sustainability of places fitting to tourism at rural areas. Due to the high complexity of the structure and dynamics of the tourism business and to reach the proposed goals of this study, the quality research with exploratory purpose was adopted. The data collecting instruments used were direct observation and recorded interviews. The interviewed people were agents from public and private realm, rural and urban, directly involved with tourism in cities with rural profile. In the public area, town agents were interviewed and in some cases, state and federal agents. In the private realm agents were interviewed representing each area that are, the tourist business, the rural area, and finally, the commercial realm. The cities chosen for the application and test of the proposed analytical model were: Lages, located in the plateau of Santa Catarina; Bonito, in the Bodoquena Hights, at Matogrosso do Sul; São Carlos, at the central region of São Paulo; Venda Nova do Imigrante, at the plateau of Espirito Santo and Carrancas at the South of Minas Gerais. The organization of the thesis follows the steps of introduction, theoretical revision, analytic model results and discussion and finally, bibliographic references. On the regard of the results gathered from the use of the model in each of the towns visited, it was possible to conclude that: the theoric revision used and presented in the chapters 2, 3 and 4 lead to the compilation of the analytical model of management of tourist clusters with rural emphasis and, concerning the cities, except for Bonito, there is no integration between public and private realms (rural, tourist and commercial). The agents have been working individually, because of the differences in objectives, interests, managing profile of those involved in the tourist business, besides disrespect for their own roles being found. The results, thus, in relation to the recognized management in the cities of Lages, São Carlos, Carrancas and Venda Nova do Imigrante, there have been the inexistence of the integration and, regarding to the local and sustainable development, including here the town Bonito, there are weak points. The first reason is the absence of a clearly directed study and the second reason because the information obtained during the interviews showed that the figures of the environmental, cultural, social and economical parameters have been noticed in different ways in each realm. There are some results that are taken as positive for the rural environment whereas are negative for the point of view of public and commercial areas and even for the community. This shows that the integration among the agents in the towns is not in a good rate. Facing the results, it is possible to consider that the suggested model is able to identify the limiting regarding integrated managing, the development of the place and sustainability.
Keywords: Planejamento estratégico; Turismo rural; Integração; Desenvolvimento sustentável; Tourism; Management; Development; Sustainability; ENGENHARIAS::ENGENHARIA DE PRODUCAO